Women's Freedom in Iraq in the Thought of Simone de Beauvoir - Ahmed, Najeeba Ibrahim (Journal of Legal and Political Studies, 2024)
Despite the passage of more than two centuries, the call for the liberation of Iraqi women still faces many challenges, including the spread of illiteracy and the nature of the relationship between men and women, in addition to the level of political and social rights. However, this does not mean that there is no progress; some improvement has been observed in many areas, but it remains limited, especially in urban areas with regard to the level of education and economic, political and social participation. Therefore, the research topic goes in line with the ideas of Simone de Beauvoir, who seeks to find a way to guarantee women's freedom and liberation, and grant them rights that enable them to achieve equality with men. This is with the aim of overcoming the male society that seeks to suppress and exclude dissenting voices, specifically the voice of women who call for lifting injustice against women and giving them the opportunity to express their rights and opinions to the same extent as men. keywords: Women's liberation, Simone de Beauvoir's freedom, Iraqi women's freedom.
Keywords: Womens liberation; Simone de Beauvoirs freedom; Iraqi womens freedom